Perspectives of clinical research on Shen-Shuai-Ning in the treatment of diabetic nephropathy - Gao, Na; Zhang, Xi-jun (Frontiers in Medicine, 2024)
Diabetic nephropathy (DN) is one of the most common chronic complications in patients with diabetes and remains a leading cause of end-stage renal disease. Despite current treatment strategies focusing primarily on blood glucose control and antihypertensive medications, their efficacy is often limited, failing to halt disease progression effectively. However, Shen-Shuai-Ning (SSN), a traditional Chinese medicine compound, has demonstrated significant clinical efficacy in DN treatment in recent years. SSN exerts multifaceted effects, including immunomodulation, attenuation of oxidative stress, and inhibition of fibrosis, leading to improvements in renal function indices and reductions in proteinuria levels, with favorable tolerability. Furthermore, when combined with conventional treatments, SSN exhibits enhanced therapeutic efficacy, providing a comprehensive and effective treatment strategy for DN patients. Future research endeavors should prioritize large-scale, multicenter clinical trials to validate its efficacy and safety across diverse populations, thereby further advancing its integration into clinical practice.